2012
DOI: 10.1186/1743-0003-9-79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of task-related continuous auditory feedback during learning of tracking motion exercises

Abstract: BackgroundThis paper presents the results of a set of experiments in which we used continuous auditory feedback to augment motor training exercises. This feedback modality is mostly underexploited in current robotic rehabilitation systems, which usually implement only very basic auditory interfaces. Our hypothesis is that properly designed continuous auditory feedback could be used to represent temporal and spatial information that could in turn, improve performance and motor learning.MethodsWe implemented thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
3
32
1
5
Order By: Relevance
“…This supports the idea that the benefits of the different sound feedback tested are not due other uncontrolled effects (like focus of attention for instance), but to the mapping between motion and sound in the auditory feedback. The fact that Target as well as Error auditory feedback significantly improved performance differs from the observations by Rosati et al (Rosati et al, 2012), where an error sonification did not prove to help for the tracking task. Our results also pointed out that the pointer-related (user-related) group improved its performance with repetition, contrary to the two other groups.…”
Section: Performance and Learningcontrasting
confidence: 52%
See 2 more Smart Citations
“…This supports the idea that the benefits of the different sound feedback tested are not due other uncontrolled effects (like focus of attention for instance), but to the mapping between motion and sound in the auditory feedback. The fact that Target as well as Error auditory feedback significantly improved performance differs from the observations by Rosati et al (Rosati et al, 2012), where an error sonification did not prove to help for the tracking task. Our results also pointed out that the pointer-related (user-related) group improved its performance with repetition, contrary to the two other groups.…”
Section: Performance and Learningcontrasting
confidence: 52%
“…Rosati et al reported studies on unidimensional tracking with a joystick, comparing the sonification of the target velocity and the tracking error (Rosati et al, 2012). They found that auditory feedback based on task parameters (features of the target or the setup) improved performance during an unpredictable task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, related experiments performed on healthy subjects revealed how auditory feedback can also be effective in reducing tracking error. In particular, continuous task-related information provided through sound in addition to visual feedback can improve not only performance but also learning of a novel visuomotor perturbation [42], [43]. Similar forms of auditory feedback can more or less be applied to gait rehabilitation, and this is indeed what this papers deals with.…”
mentioning
confidence: 88%
“…satisfies Equation (10). However, in the P-F-type two-channel architecture, E 3 = C 2 = 0, so the optimal law for transparency reduces to:…”
Section: Definition Of the Control Lawmentioning
confidence: 99%